Book Reviews. Issue 2 (1st June 2019) - Fransen, Koos; Peacock, Sean; Wood, Peter; Zhang, Jie
Abstract : Karel Martens, Transport Justice: Designing Fair Transportation Systems (New York: Routledge, 2017), 240 pp., 27 illustrations, $47.45 Nancy Cook and David Butz, eds., Mobilities, Mobility Justice and Social Justice (London: Routledge, 2019), 270 pp., 15 black-and-white illustrations, £115 Cosmin Popan, Bicycle Utopias: Imagining fast and slow bicycle futures (London: Routledge, 2019), 201 pp., £92. Carlos López Galviz, Cities, Railways, Modernities: London, Paris, and the Nineteenth Century (New York: Routledge, 2019), 294 pp., 37 illus., £92